Alphaworld: what am i?: weird and wonderful sea animals - Feely, Jenny (Horwitz Education St. Leonards, N.S.W., 2004)
"Weird and Wonderful Sea Animals" explores the fascinating diversity of marine life. The book highlights unique creatures, such as the colorful octopus, bioluminescent jellyfish, and the quirky seahorse. Each animal is presented with fun facts about their habitats, behaviors, and adaptations, showcasing the wonders of the ocean. The engaging illustrations and descriptions aim to inspire curiosity and appreciation for the mysteries of sea life.